Synergistic effects of coffee aromatherapy and oxytocin massage on serum prolactin levels in postpartum mothers: A quasi-experimental study - Rizki Fitrianingtyas; Yuningsih; Trisna Pangestuning Tyas; Yolanda Indri Octaviani; Dinar Perbawati; Fitri Kusumasari; Dini Eka Pripuspitasari (Nursing and Health Sciences Journal (NHSJ), 2026)
Successful lactation relies on adequate secretion of prolactin and oxytocin, which postpartum stress frequently inhibits. This study evaluated the synergistic effect of combined coffee aromatherapy and oxytocin massage on serum prolactin levels in postpartum mothers. A quasi-experimental pretest–posttest control group design was conducted in Jember, Indonesia, involving 20 postpartum mothers allocated into intervention (n=10) and control (n=10) groups. The intervention group received 15 minutes of coffee aromatherapy followed by 15 minutes of oxytocin massage twice weekly for two weeks. The control group received routine postpartum care. Serum prolactin concentrations were quantified via ELISA at baseline and day 14. Baseline prolactin levels were comparable between groups. Following the intervention, the intervention group exhibited a significant increase in prolactin from 133.00 ± 6.82 ng/mL to 165.80 ± 20.82 ng/mL (mean change: +32.80 ng/mL). Conversely, the control group experienced a decline from 141.51 ± 6.16 ng/mL to 122.83 ± 14.98 ng/mL (mean change: −18.68 ng/mL). Independent t-test analysis revealed a highly significant between-group difference in prolactin change scores (mean difference: 51.47 ng/mL; 95% CI: 35.40–67.54; t = 6.73, p < 0.001), yielding a very large effect size (Cohen's d = 3.01). Integrating coffee aromatherapy with oxytocin massage significantly elevates prolactin levels, offering a potent, non-invasive complementary strategy to optimize the neuroendocrine environment for lactation. Larger randomized controlled trials are required to validate these findings and assess long-term breastfeeding outcomes.